Amyloidosis: What does pathology offer? The evolving field of tissue biopsy - Riefolo, Mattia; Conti, Matteo; Longhi, Simone; Fabbrizio, Benedetta; Leone, Ornella (Frontiers in Cardiovascular Medicine, 2022)
Since the mid-nineteenth century pathology has followed the convoluted story of amyloidosis, recognized its morphology in tissues and made identification possible using specific staining. Since then, pathology studies have made a significant contribution and advanced knowledge of the disease, so providing valuable information on the pathophysiology of amyloid aggregation and opening the way to clinical studies and non-invasive diagnostic techniques. As amyloidosis is a heterogeneous disease with various organ and tissue deposition patterns, histology evaluation, far from offering a simple yes/no indication of amyloid presence, can provide a wide spectrum of qualitative and quantitative information related to and changing with the etiology of the disease, the comorbidities and the clinical characteristics of patients. With the exception of cardiac transthyretin related amyloidosis cases, which today can be diagnosed using non-biopsy algorithms when stringent clinical criteria are met, tissue biopsy is still an essential tool for a definitive diagnosis in doubtful cases and also to define etiology by typing amyloid fibrils. This review describes the histologic approach to amyloidosis today and the current role of tissue screening biopsy or targeted organ biopsy protocols in the light of present diagnostic algorithms and various clinical situations, with particular focus on endomyocardial and renal biopsies. Special attention is given to techniques for typing amyloid fibril proteins, necessary for the new therapies available today for cardiac transthyretin related amyloidosis and to avoid patients receiving inappropriate chemotherapy in presence of plasma cell dyscrasia unrelated to amyloidosis. As the disease is still burdened with high mortality, the role of tissue biopsy in early diagnosis to assure prompt treatment is also mentioned.